Wage Bargaining and Turnover Costs with Heterogeneous Labour: The No-screening Case - J. Strand (University of Oslo, Department of Economics, 1998)
We study the effects of mobility costs in a model of wage bargaining between workers and firms, where there is instantaneous matching, free firm entry, heterogeneous labour, and workers' individual productivities are discovered by firms only after being hired. We derive the employment level and the minimum quality standard, in the market solution and in the socially efficient solution.
Keywords: J31; J62; 330; wages; bargaining; labour market